Consideration on the Path of Non- original Database Rights Protection (International Research in Economics and Finance, 2022)
In the current civil and commercial cases involving disputes over the ownership of data, judges tend to use the Anti-unfair Competition Law to regulate and protect the property rights and interests of databases. However, due to the limited scope of adjustment, incomprehensive protection, and other defects of the Anti-unfair Competition Law, the Anti-unfair Competition Law is not sufficient to regulate database rights and interests. In response, the Western countries have adopted special Database Protection Directive which has been transformed into a special protection for databases. There is also a new model of protection under patent laws. In the era of the booming development of big data, the problem of database rights and interests protection urgently needs a more comprehensive legislative solution.